Comparable Enhanced Prothrombogenesis in Simple Central Obesity and Metabolic Syndrome - Noor Shafina Mohd Nor; Hanis Saimin; Thuhairah Rahman; Suraya Abdul Razak; Nadzimah Mohd Nasir; Zaliha Ismail; Hapizah Mohd Nawawi (Hindawi Limited, 2018)
Objective. There is limited data comparing prothrombogenic or fibrinolysis biomarkers (tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1)) simultaneously in subjects with Metabolic Syndrome (MS), simple central obesity without MS (COB) and normal controls (NC). We investigated the concentrations of fibrinolysis biomarkers in subjects with MS, COB and NC. Methods. A cross-sectional study involving 503 drug naive subjects (163 males, aged 30-65 years old (mean age ± SD = 47.4 ± 8.3 years)) divided into MS, COB and NC groups. COB was defined as central obesity (waist circumference (WC) males ≥90 cm, females ≥80 cm) in the absence of MS according to the International Diabetes Federation 2006. Fasting blood levels of tPA and PAI-1were analyzed. Results. MS and COB had significantly higher concentration of all biomarkers compared to NC. The MS group had significantly higher concentration of tPA and PAI-1 compared to COB. WC and HDL-c had significant correlation with all biomarkers (tPA p<0.001, PAI-1 p<0.001). Fasting plasma glucose and diastolic blood pressure were independent predictors after correcting for confounding factors. Conclusion. Central obesity with or without MS both demonstrated enhanced prothrombogenesis. This suggests that simple obesity possibly increases the risk of coronary artery disease in part, via increased susceptibility to thrombogenesis.